Predator size and prey size–gut capacity ratios determine kill frequency and carcass production in terrestrial carnivorous mammals. Issue 1 (19th September 2018) - De Cuyper, Annelies; Clauss, Marcus; Carbone, Chris; Codron, Daryl; Cools, An; Hesta, Myriam; Janssens, Geert P. J.
Abstract : Carnivore kill frequency is a fundamental part of predator–prey interactions, which are important shapers of ecosystems. Current field kill frequency data are rare and existing models are insufficiently adapted to carnivore functional groups. We developed a kill frequency model accounting for carnivore mass, prey mass, pack size, partial consumption of prey and carnivore gut capacity. Two main carnivore functional groups, small prey‐feeders versus large prey‐feeders, were established based on the relationship between stomach capacity (C) and pack corrected prey mass (iMprey). Although the majority of small prey‐feeders is below, and of large prey‐feeders above a body mass of 10–20 kg, both occur across the whole body size spectrum, indicating that the dichotomy is rather linked to body size‐related ecology than physiology. The model predicts a negative relationship between predator size and kill frequency for large prey‐feeders. However, for small prey‐feeders, this negative relationship was absent. When comparing carnivore prey requirements to estimated stomach capacity, small carnivores may have to eat to their full capacity repeatedly per day, requiring fast digestion and gut clearance. Large carnivores do not necessarily have to eat to full gastric capacity per day, or do not need to eat every day, which in turn reduces kill frequencies or drives other ecological processes such as scavenging, kleptoparasitism, and partial carcass consumption. Where ecological conditions allow, large prey‐feeding appears attractive for carnivores, which can thus reduce activities related to hunting. This is particularly so for large carnivores, who can achieve distinct reductions in hunting activity due to their relatively large gut capacity.